Analysis of Potential Risk Factors of COVID-19 Based on Variants: Omicron, Delta, and Alpha - Kannan, Dharshini; Muppiri, Sreenidhi; Reid, Maren (Archives of Clinical and Biomedical Research, 2023)
The coronavirus disease 2019 (COVID-19) pandemic has changed which affects the risk of COVID-19 infection for specific subgroups. We focused on the subgroups based on the factors (sex, age, and vaccination) and COVID-19 strains (Alpha, Delta, and Omicron). Past studies focused on analysing these factors based on one geographic region or one COVID-19 strain. Therefore, there is a need to understand these factors’ association with risk of COVID-19 infection through analysing data from various geographic regions and strains. The association between COVID-19 strains and the factors was assessed through chi-square test and odds ratio tests. Sex, vaccination, age had a significant association with testing positive for the COVID-19 strains of interest in most geographies. The biggest difference was unvaccinated individuals have 3.14 higher odds of getting Alpha than vaccinated individuals in Canada. These findings provide insights into the groups that are more susceptible to contracting specific strains of COVID-19.The coronavirus disease 2019 (COVID-19) pandemic has changed which affects the risk of COVID-19 infection for specific subgroups. We focused on the subgroups based on the factors (sex, age, and vaccination) and COVID-19 strains (Alpha, Delta, and Omicron). Past studies focused on analysing these factors based on one geographic region or one COVID-19 strain. Therefore, there is a need to understand these factors’ association with risk of COVID-19 infection through analysing data from various geographic regions and strains. The association between COVID-19 strains and the factors was assessed through chi-square test and odds ratio tests. Sex, vaccination, age had a significant association with testing positive for the COVID-19 strains of interest in most geographies. The biggest difference was unvaccinated individuals have 3.14 higher odds of getting Alpha than vaccinated individuals in Canada. These findings provide insights into the groups that are more susceptible to contracting specific strains of COVID-19.